LA PHILOSOPHIE POUR ENFANTS : UNE PISTE POUR RÉCONCILIER ENSEIGNEMENT DISCIPLINAIRE ET VIE SCOLAIRE ? - Christophe POINT (Studia Universitatis Babeș-Bolyai. Philosophia, 2021)
Philosophy for Children: a Way to Reconcile Disciplinary Teaching and School Life? Drawing mainly on John Dewey's writings, this contribution aims to extend the dualism of a traditional conception of education at the epistemological, pedagogical and organizational levels. This conception was already criticised by this author at the beginning of the 20th century and still remains widely present today among the school community. Through this approach, we demonstrate that the dualist approach is as many obstacles to be removed in the process both to improve and rebuild a better education. The hypothesis defended here consists to demonstrate how philosophy for children, strengthened by its pragmatist heritage, can challenge these dualisms and thereby jeopardize the traditional conception of education.